Knowledge and attitudes of Turkish endodontists towards digital radiology and cone beam computed tomography - BAŞTÜRK, FATIMA BETÜL; PEKER, MEHMET SERTAÇ; ERÇALIK YALÇINKAYA, ŞEBNEM (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2014)
Introduction: The aim of this study was to assess the knowledge and attitudes of Turkish endodontists toward digital radiological imaging (DRI) and cone-beam computed tomography (CBCT). Materials and Methods: One hundred and fifty questionnaires were distributed. Questionnaires were given to a sample of endodontists and PhD students in endodontics who attended the 11th International Congress of the Turkish Endodontic Society in Istanbul in 2012. Following the congress, the same questionnaires were sent electronically to endodontists who did not attend the congress. The participants were asked to answer 28 multiple-choice questions concerning their knowledge and practice regarding recent imaging techniques. The questions were subdivided into 2 main topics; general information; general approach to digital imaging. The statistical analysis was carried out by an. 2 chi(2)-test to compare the means at a significance level of P < 0.05. Results: The response rate for this study was 74%. The mean age of the endodontists who participated in this study was 32.74 +/- 10.40 (range 22-61 years). Of the endodontists, 76.6% used digital imaging techniques (DUEs) in their clinics. Statistically significant differences were found between the DUEs and endodontists not using digital imaging (NDUEs), regarding age, gender, graduation year and place of employment (P < 0.01). Endodontists 40-years-old and above had significantly lower knowledge of CBCT compared to the younger groups (P = 0.001). Conclusions: The number of endodontists using digital imaging has been increasing in Turkey. The findings of the present study highlighted the need for adapting to new technologies via continuing education.
Keywords: Cone-beam computed tomography; digital imaging; knowledge; questionnaire; GENERAL DENTAL PRACTITIONERS; RADIOGRAPHY